PROFIL GOOGLE SCHOLAR DOSEN UIN SYARIF HIDAYATULLAH JAKARTA BERBASIS WEBOMETRICS - Albantani, Azkia Muharom (Perspektif Ilmu Pendidikan, 2016)
This research aims to obtain an overview of the profiles of lecturers based on webometrics, a general description of webometrics-based facilities at UIN Jakarta, and the profiles of the lecturers on Google Scholar. The method used in this study is a survey method, especially in taking the respondents as a data source. In presenting the data, this study uses descriptive analysis method which illustrates the results obtained from the survey of the profiles of FITK (Faculty of Education and Teachers Training) lecturers on Google Scholar. The study was conducted within a period of 6 months (April 1st to September 31st, 2015). List of Ranks shows the number of permanent lecturers (civil servants) of FITK UIN Jakarta is 163 lecturers. Nevertheless, after conducting a tracking study, there are 35 lecturers only who already have a profile account on Google Scholar. Out of 35 lecturers, only 19 lecturers have values in citations, h-index, and h10-index. Prof. Dr. Abuddin Nata, M.A. is the most prolific and most widely cited lecturer on Google Scholar in the Faculty of Education and Teachers Training (FITK) of UIN Jakarta. His scientific works have been cited 1600 times in other works. He has also the highest h-index value, 17 (seventeen), and the highest i10-index, 21 (twenty one).